Paired Ru‒O‒Mo ensemble for efficient and stable alkaline hydrogen evolution reaction. (April 2021) - Li, HuangJingWei; Liu, Kang; Fu, Junwei; Chen, Kejun; Yang, Kexin; Lin, Yiyang; Yang, Baopeng; Wang, Qiyou; Pan, Hao; Cai, Zhoujun; Li, Hongmei; Cao, Maoqi; et al.
Abstract: Electrocatalytic hydrogen evolution reaction (HER) in alkaline media is a promising electrochemical energy conversion strategy. Ruthenium (Ru) is an efficient catalyst with a desirable cost for HER, however, the sluggish H2 O dissociation process, due to the low H2 O adsorption on its surface, currently hampers the performances of this catalyst in alkaline HER. Herein, we demonstrate that the H2 O adsorption improves significantly by the construction of Ru–O–Mo sites. We prepared Ru/MoO2 catalysts with Ru–O–Mo sites through a facile thermal treatment process and assessed the creation of Ru–O–Mo interfaces by transmission electron microscope (TEM) and extended X-ray absorption fine structure (EXAFS). By using Fourier-transform infrared spectroscopy (FTIR) and H2 O adsorption tests, we proved Ru–O–Mo sites have tenfold stronger H2 O adsorption ability than that of Ru catalyst. The catalysts with Ru–O–Mo sites exhibited a state-of-the-art overpotential of 16 mV at 10 mA cm –2 in 1 M KOH electrolyte, demonstrating a threefold reduction than the previous bests of Ru (59 mV) and commercial Pt (31 mV) catalysts. We proved the stability of these performances over 40 h without decline. These results could open a new path for designing efficient and stable catalysts. Graphical Abstract: Ru/MoO2 catalyst with paired Ru–O–Mo sites improved the H2 O dissociation by optimized H2 O adsorption, and great alkaline HER performance was achieved. ga1 Highlights: The H2 O adsorption ability significantly improves by the paired Ru–O–Mo sites ensemble. The charge transfer from Ru to the O in Ru–O–Mo sites reduces the H2 O dissociation barrier. The Ru/MoO2 catalysts with Ru–O–Mo sites exhibited an excellent overpotential (16 mV) and stability (40 h) in alkaline HER.